Human herpesvirus‐8–positive primary effusion lymphoma in HIV‐negative patients: Single institution case series with a multidisciplinary characterization. Issue 1 (10th September 2020) - Rossi, Giovanni; Cozzi, Ilaria; Della Starza, Irene; De Novi, Lucia Anna; De Propris, Maria Stefania; Gaeta, Aurelia; Petrucci, Luigi; Pulsoni, Alessandro; Pulvirenti, Federica; Ascoli, Valeria
Abstract : BACKGROUND: Primary effusion lymphoma (PEL) is a very rare non‐Hodgkin lymphoma caused by human herpesvirus‐8 (HHV8) that grows in liquid phase within body cavities. The diagnosis of PEL is based on cytology but requires confirmatory ancillary tests. PEL occurs mainly in association with HIV infection. This study describes 9 cases of PEL in HIV‐negative patients and compares their characteristics with 10 HIV‐associated cases of PEL diagnosed at a single institution in Italy between 1995 and 2019. METHODS: Clinical records were reviewed for demographic data, comorbidities, laboratory abnormalities, and outcome. PEL samples were evaluated for cytomorphology, immunophenotype, immunoglobulin ( IG )/T cell receptor ( TR ) rearrangements, and HHV8 and Epstein‐Barr virus (EBV) viral loads in effusion supernatants. RESULTS: HIV‐unrelated PEL occurred in 8 elderly patients (7 men, 1 woman) and 1 young adult with primary antibody deficiency. Cytology revealed HHV8‐positive lymphoma cells lacking B/T cell antigens and exhibiting 2 cell patterns (polymorphous or monotonous). IG was clonally rearranged in all cases; aberrant TRG occurred in 2 cases. Effusion supernatants had more than 10 6 HHV8 DNA copies per mL and variable loads of EBV DNA. Compared with HIV‐associated PEL, the HIV‐negative cohort was characterized by older age, less frequent association with Kaposi sarcoma and/or multicentric Castleman disease, comparable but less abnormal laboratory parameters, and a nonsignificant survival benefit. PEL cases with low apoptosis were associated with better prognosis. CONCLUSION: To the best of our knowledge, our case series of HIV‐unrelated PEL is the largest thus far, expands the spectrum of cytological findings, and supports the need for a multidisciplinary approach in the diagnostic workup. Abstract : This study describes human herpesvirus‐8 (HHV8)‐positive primary effusion lymphoma (PEL) in HIV‐negative patients—including clinical and laboratory abnormalities, cytology and immunophenotype, IG / TR rearrangements, and HHV8 and Epstein‐Barr virus viral loads in effusion supernatants—and provides a thorough comparison between HIV‐unrelated and HIV‐associated PEL cases. It allows enlarging the spectrum of morphological findings (cell pattern and inflammatory background, mitosis/apoptosis) and highlights the key role of cytology in the context of a multidisciplinary workup of PEL.